SOSIALISASI BUDIDAYA BUAH NAGA (Hylocereus costaricensis Lem) PELUANG USAHA DI LAHAN KERING DESA MATA AIR, KECAMATAN KUPANG TENGAH, KABUPATEN KUPANG - Roefaida, Effy; Arsa, I Gusti Bagus Adwita; Mukun, Lince; Nguru, Elias Stefanus Oskar; Tanggela, Yosua (Universitas Mataram, 2025)
The constraints faced by members of the Anugerah Tribuana group, Mata Air village, Taebenu sub-district, Kupang district are limited knowledge and skills in dragon fruit cultivation techniques (from selecting plant types, selecting seedling materials, nurseries, transplanting seedlings, soil processing, planting, irrigation, maintenance, pest and disease control, and the right time to harvest; including knowledge and skills in environmentally friendly cultivation techniques based on organic fertilizers and botanical pesticides. Increasing dragon fruit productivity in the Anugerah Tribuana farmer group, Mata Air village, Taebenu sub-district, Kupang district through assistance in implementing dragon fruit cultivation techniques. Using lecture and demonstration plot methods by selecting the type of cuttings planted, preparing cutting materials, nurseries, planting, irrigation, fertilization and environmentally friendly pest and pathogen control, as well as determining the time of harvest, harvesting and post-harvest handling. Socialization was carried out to 20 farmer participants. The results of the activity are adequate socialization of knowledge and techniques for dragon fruit cultivation, reflected in the level of attendance of participating farmers and high enthusiasm in the community partnership program; shown by discussing various aspects of dragon fruit cultivation that are appropriate and effective in responding to limitations in dry land, a combination of liquid organic fertilizer (POC) and rice husk charcoal biocar and control of OPT in dry land with the manufacture and application of botanical pesticides. The material is presented and there is two-way productive enthusiastic communication, especially the technical manufacture and application of botanical pesticides and dragon fruit cultivation in farmers and the models and techniques for their use. Socialization of dragon fruit cultivation has a positive impact on increasing knowledge and skills of farmers adequately in the Anugerah Tribuana farmer group in Mata Air Village, Taebenu District, Kupang Regency.